Heavy metal nickel pollution resistant catalytic cracking catalyst and preparation method thereof

By using boron-phosphoraluminum composition in catalytic cracking catalysts, the boron is fixed in the pores of the composition, and the problem of poor anti-pollution effect of the catalyst under high nickel content is solved, and the effect of reducing hydrogen and catalytic coking yields and improving the yield of high value-added products is achieved.

CN119869605AActive Publication Date: 2025-04-25PETROCHINA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311374428.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25
Estimated Expiration
2043-10-23

AI Technical Summary

Technical Problem

The existing catalytic cracking catalysts have poor anti-pollution effects on heavy metal nickel under the conditions of treating high nickel content, resulting in a poor catalyst selectivity and an increase in yield of hydrogen and catalytic coke.

Method used

Boron phosphorus aluminum composition (a mixture of AlPO4 and B, P, Al) is used as an additive component and added to the catalyst. By calcining, a mesoporous structure is formed to fix boron in the pores of the composition, thereby reducing its toxic effect on molecular sieve.

Benefits of technology

Effectively reduce the dehydrogenation activity of nickel, reduce the yield of hydrogen and catalytic coke, improve the yield of high-value-added products, and maintain the activity stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004509545600000061
    Figure BDA0004509545600000061
  • Figure BDA0004509545600000081
    Figure BDA0004509545600000081
  • Figure BDA0004509545600000131
    Figure BDA0004509545600000131
Patent Text Reader

Abstract

The invention discloses a heavy metal nickel pollution resistant catalytic cracking catalyst and a preparation method thereof. The preparation method comprises the following steps: mixing a first raw material with water, pulping, and then carrying out spray molding, roasting, washing and drying to obtain the catalytic cracking catalyst, the first raw material comprises a boron-phosphorus-aluminum composition, a molecular sieve, clay and a binder. The boron-phosphorus-aluminum composition is a mixture of AlPO4, B, P and Al, and is subjected to roasting treatment in the preparation process. The existence of the element B can effectively inhibit the pollution of nickel metal, and AlPO4 can effectively inhibit the dealumination of the molecular sieve and counteract the toxic action of B on the catalyst; in the preparation process of the boron-phosphorus-aluminum composition, a mesoporous structure is formed through roasting, and boron is fixed in a pore channel of the composition, so that the boron is not easy to migrate to the surface of a molecular sieve in the preparation process of the catalyst to damage the skeleton structure of the molecular sieve, and the catalyst can maintain relatively high activity stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalytic cracking catalysts, and in particular to a catalytic cracking catalyst resistant to heavy metal nickel pollution and a preparation method thereof. Background Art

[0002] Catalytic cracking (FCC) is an important means of oil processing. With the increasing depletion of oil resources, the crude oil for catalytic cracking is becoming heavier and inferior, and the content of metals such as nickel and vanadium is increasing. The nickel in the crude oil mainly exists in heterocyclic compounds such as porphyrin nickel. During the catalytic cracking process, metallic nickel will be deposited on the surface of the catalyst. The toxicity of nickel is manifested as a strong catalytic dehydrogenation effect, which makes the selectivity of the catalytic cracking reaction worse and increases the yield of hydrogen and catalytic coke (coke generated by the catalytic cracking reaction on the acid center).

[0003] At present, the main technologies for FCC to resist heavy metal nickel pollution are: (1) application of nickel passivators; (2) preparation of nickel-pollution-resistant catalytic cracking catalysts.

[0004] Nickel passivators are mainly compounds of antimony, bismuth, tin, rare earth, boron, etc., which are dispersed in solvents and added to crude oil. In the reactor, these metal compounds can react with nickel to form relatively stable compounds, reducing the dehydrogenation activity of nickel. However, the toxicity of antimony-based, bismuth-based and tin-based nickel passivators is relatively strong, causing great pollution to the environment, thus limiting their application. Rare earth-based and boron-based nickel passivators are relatively less toxic and can achieve the same passivation effect of the first three, but they require suitable solvents and dispersants to dissolve and disperse these compounds, increasing production and transportation costs. Moreover, if it is an aqueous passivator, it is easy to freeze, which affects the large-scale application of the passivator.

[0005] The preparation technology of FCC catalysts resistant to heavy metal pollution is to adjust the physical and chemical properties of the FCC catalyst matrix such as specific surface area, pore volume and chemical composition through different modification methods. Since heavy metals are first deposited on the surface of the catalyst matrix during the FCC process, the heavy metals are captured on the surface of the matrix in a timely manner to protect the active components of the molecular sieve. At present, different preparation technologies for FCC catalysts resistant to heavy metal pollution have been developed successively and have become a hot topic in the research field of FCC. For example, the FCC catalyst is modified with elements or compounds such as alkaline earth metals, copper, zinc, cadmium and tungsten to improve the catalyst's resistance to heavy metal pollution; however, the metal-modified catalytic cracking catalyst is not effective in resisting heavy metal nickel pollution, especially under the condition of high nickel content, the nickel passivation effect is even worse. Summary of the invention

[0006] The object of the present invention is to provide a catalytic cracking catalyst resistant to heavy metal nickel pollution and a preparation method thereof.

[0007] The present invention prepares a boron-phosphorus-aluminum composition, and adds the composition as an additive component into a catalytic cracking catalyst to prepare a catalytic cracking catalyst resistant to nickel metal pollution. The composition is a mixture of AlPO4, B, P and Al. The presence of the B element can effectively inhibit the pollution of nickel metal, and the AlPO4 can effectively inhibit the dealumination of the molecular sieve, thereby offsetting the poisoning effect of B on the catalyst.

[0008] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0009] The first aspect of the present invention provides a method for preparing a catalytic cracking catalyst resistant to heavy metal nickel pollution, comprising the following steps:

[0010] The first raw material is mixed with water, slurried, and then spray-formed, roasted, washed, and dried to obtain the catalytic cracking catalyst;

[0011] The first raw material includes a boron-phosphorus-aluminum composition, a molecular sieve, clay and a binder;

[0012] The boron-phosphorus-aluminum composite is a mixture of AlPO4 and B, P, and Al, and is calcined during the preparation process.

[0013] According to the preparation method of the present invention, the first raw material may further include pseudo-boehmite.

[0014] According to the preparation method of the present invention, preferably, the boron-phosphorus-aluminum composition is prepared by reacting an aluminum compound, phosphoric acid, and a boron compound and calcining at 400-700°C;

[0015] The boron compound is added according to the boron content of the total mass of the boron-phosphorus-aluminum composition of 2wt% to 6wt%, more preferably 2wt% to 4wt%;

[0016] The aluminum compound and phosphoric acid are added in a molar ratio of Al:P of (0.5-2.0):1, more preferably (0.9-1.5):1.

[0017] According to the preparation method of the present invention, preferably, the boron-phosphorus-aluminum composition is prepared by the following method 1 or method 2:

[0018] Method 1: Add aluminum compound to water, then add phosphoric acid dropwise; add boron compound and stir to obtain a sol containing boron, phosphorus and aluminum;

[0019] Drying the sol containing boron, phosphorus and aluminum, and calcining at 400-700° C. for 1 h-4 h to obtain the boron-phosphorus-aluminum composite;

[0020] Method 2: adding an aluminum compound to water, and then dropping phosphoric acid to obtain a sol containing phosphorus and aluminum; drying the sol containing phosphorus and aluminum to obtain an intermediate product;

[0021] The boron compound is dissolved in water, loaded in the intermediate product by an impregnation method, dried, and calcined at 400 to 700° C. for 1 to 4 hours to obtain the boron-phosphorus-aluminum composite.

[0022] In the preparation process of the catalytic cracking catalyst of the present invention, when the first raw material is mixed with water for slurrying, the solid content of the system is preferably 10wt% to 45wt%. The calcination temperature of the catalytic cracking catalyst is preferably 400 to 800°C, and the time is preferably 0.5 to 3h. The drying temperature is preferably 100 to 150°C, and the time is preferably 8 to 24h. The washing is performed by water washing.

[0023] In the preparation process of the boron-phosphorus-aluminum composition of the present invention, a mesoporous structure can be formed after calcination, and boron is fixed in the pores of the composition. It is not easy to migrate to the surface of the molecular sieve during the preparation process of the catalyst, destroying the skeleton structure of the molecular sieve, so that the catalyst can maintain a relatively high activity stability. In method one and method two, the calcination temperature is preferably 400-700°C, and the time is preferably 1-4h. In addition, the drying temperature is 80-120°C, and the time is 5-24h.

[0024] In the preparation process of the boron-phosphorus-aluminum composition of the present invention, in method 1 and method 2, after the phosphoric acid is added dropwise, the mixture can be aged for a period of time, for example, 1 to 5 hours, under stirring. In method 1, it is preferred that stirring is continued for 0.5 to 3 hours after the boron compound is added.

[0025] In the process of preparing the boron-phosphorus-aluminum composition, preferably, the aluminum compound is selected from one or a combination of two or more of aluminum oxide, pseudo-boehmite, aluminum nitrate, and aluminum chloride. More preferably, the aluminum compound is aluminum nitrate or pseudo-boehmite.

[0026] In the process of preparing the boron-phosphorus-aluminum composition, preferably, the concentration of the phosphoric acid is 20 wt% to 85 wt%, preferably 30 wt% to 70 wt%.

[0027] In the process of preparing the boron-phosphorus-aluminum composition, preferably, the boron compound is a soluble boron compound selected from one or a combination of two or more of boron phosphate, boric acid, boric anhydride, ammonium borate, and ammonium fluoroborate. More preferably, the boron compound is boric acid or boric anhydride.

[0028] In the catalytic cracking catalyst preparation process, preferably, the specific preparation process of the catalytic cracking catalyst includes:

[0029] Adding a second raw material into water and mixing evenly, adding a binder after aging to form a catalyst matrix slurry; the second raw material is part of the components in the first raw material, including the boron-phosphorus-aluminum composition and clay, or the second raw material includes the boron-phosphorus-aluminum composition, clay and pseudo-boehmite;

[0030] The molecular sieve is added into water, sheared, and then added into the catalyst matrix slurry, slurried, spray-formed, calcined, washed, and dried to obtain the catalytic cracking catalyst.

[0031] More preferably, the aging temperature is 40 to 90° C., further preferably 75° C., and the aging time is 1 to 5 hours, further preferably 1 hour.

[0032] In the process of preparing the catalytic cracking catalyst, preferably, the boron-phosphorus-aluminum composition accounts for 5wt% to 25wt% of the mass of the catalytic cracking catalyst on a dry basis.

[0033] In the process of preparing the catalytic cracking catalyst, preferably, the corresponding raw materials of each component in the obtained catalytic cracking catalyst, calculated on a dry basis of oxides, the content of the molecular sieve is 20wt% to 50wt%, the content of the boron-phosphorus-aluminum composition is 5wt% to 25wt%, the content of the clay is 19wt% to 55wt%, the content of the pseudo-boehmite is 0 to 13wt%, and the content of the binder is 8wt% to 15wt%. In the process of preparing the catalytic cracking catalyst, preferably, the molecular sieve is selected from one or a combination of two or more of RDSY molecular sieve, REY molecular sieve, β molecular sieve, and ZSM-5 molecular sieve.

[0034] In the process of preparing the catalytic cracking catalyst, preferably, the clay is selected from kaolin, etalonite, montmorillonite, attapulgite, or a combination of two or more thereof.

[0035] In the process of preparing the catalytic cracking catalyst, preferably, the binder is selected from one or a combination of two or more of aluminum sol, silica sol or colloidal aluminum oxide or silicon oxide materials.

[0036] The second aspect of the present invention provides a catalytic cracking catalyst resistant to heavy metal nickel pollution, which is prepared by the preparation method provided in the first aspect above.

[0037] The components of the catalytic cracking catalyst resistant to heavy metal nickel pollution correspond to raw materials, and the content of the molecular sieve is 20wt% to 50wt% based on dry oxide.

[0038] According to the catalytic cracking catalyst resistant to heavy metal nickel pollution of the present invention, preferably, the corresponding raw materials of each component in the catalytic cracking catalyst resistant to heavy metal nickel pollution, calculated on a dry basis of oxides, contain 5wt% to 25wt% of the boron-phosphorus-aluminum composition.

[0039] According to the catalytic cracking catalyst resistant to heavy metal nickel pollution of the present invention, preferably, the content of the clay in the raw materials corresponding to the components in the catalytic cracking catalyst resistant to heavy metal nickel pollution is 19wt% to 55wt% based on dry oxides.

[0040] According to the catalytic cracking catalyst resistant to heavy metal nickel pollution of the present invention, preferably, the components of the catalytic cracking catalyst resistant to heavy metal nickel pollution correspond to raw materials, and the content of the pseudo-boehmite is 0-13wt% based on dry oxide.

[0041] According to the catalytic cracking catalyst resistant to heavy metal nickel pollution of the present invention, preferably, the content of the binder in the components corresponding to the raw materials in the catalytic cracking catalyst resistant to heavy metal nickel pollution is 5wt% to 21wt% on a dry basis of oxides.

[0042] The present invention adds the boron-phosphorus-aluminum composition as an additive component to the catalyst preparation to obtain a catalytic cracking catalyst resistant to heavy metal nickel pollution. Since the composition contains component B that can effectively combine with nickel, nickel can be effectively converted into a relatively stable compound, the dehydrogenation activity of nickel is reduced, the poisoning effect of nickel on the catalytic cracking catalyst is reduced, the yield of hydrogen and coke can be effectively reduced, and the yield of high value-added products can be increased. At the same time, the presence of AlPO4 can effectively inhibit the dealumination of the molecular sieve and offset the poisoning effect of the addition of B on the catalyst.

[0043] During the preparation of the boron-phosphorus-aluminum composite, a mesoporous structure is finally formed through calcination. Boron is fixed in the pores of the composite and is not easy to migrate to the surface of the molecular sieve during the preparation of the catalyst to destroy the skeleton structure of the molecular sieve, so that the catalyst can maintain a relatively high activity stability. DETAILED DESCRIPTION

[0044] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0045] All numerical specifications herein (e.g., temperature, time, concentration, and weight, etc., including ranges for each thereof) are generally approximate values ​​that may be appropriately varied (+) or (-) in increments of 0.1 or 1.0. All numerical specifications may be understood as being preceded by the term "about."

[0046] The raw materials and properties used in the following examples are:

[0047] Kaolin, silica sol (solid content 40wt%), alumina sol (solid content 18wt%), various molecular sieves, pseudo-boehmite (dry basis is the part after ignition loss, its molecular weight is 101.96) and hydrochloric acid (30wt%) are all industrial grade; nickel nitrate, boric acid, boric anhydride, aluminum nitrate, aluminum chloride, ammonium metavanadate, oxalic acid are of analytical grade. Phosphoric acid 85wt%.

[0048] Catalyst micro-reaction activity evaluation method: The micro-reaction activity evaluation device developed by Beijing Huier Sanji Green Chemical Technology Co., Ltd. was used for evaluation. The raw oil used was 3 million tons / year of catalyst from Lanzhou Petrochemical Company. The properties of the raw oil are shown in Table 1. The catalyst was aged at 800°C and 100% steam for 17 hours before evaluation.

[0049] Catalyst reaction performance evaluation method (ACE):

[0050] The catalyst was contaminated with heavy metals before evaluation. The method of heavy metal contamination simulated the nickel content in industry: an aqueous solution of nickel nitrate (12000ppm Ni based on the dry basis of the catalyst) was impregnated into the catalyst, dried at 120°C, and calcined at 550°C for 4 hours. The reaction performance was evaluated using an ACE device. The raw oil used was 3 million tons / year of catalytic material from Lanzhou Petrochemical Company. The properties of the raw oil are shown in Table 1. The catalyst was aged at 800°C and 100% steam for 10 hours before evaluation.

[0051] Table 1 Raw oil properties

[0052]

[0053] Preparation of boron-phosphorus-aluminum composition:

[0054] Composition 1

[0055] 2129.96 g of aluminum nitrate (Al: 10 mol) was added to 3 L of water under stirring until dissolved, 1152.94 g of 85 wt% phosphoric acid (P: 10 mol) was added dropwise to the dissolved aluminum nitrate to form a homogeneous sol, and then 85.68 g of boric acid (B: 1.4 mol) was added and stirring was continued for 0.5 h. The sol was dried in an oven at 80 ° C for 24 h and calcined at 700 ° C for 1 h to obtain composition 1.

[0056] Composition 2

[0057] 1019.60 g of dry pseudo-boehmite (Al: 20 mol) was dispersed in 3 L of water under stirring and the stirring was continued for 0.5 h. 1400.00 g of 70 wt% phosphoric acid (P: 10 mol) was added dropwise under stirring to form a homogeneous sol. The stirring was continued for 1 h. Then 219.30 g of boric anhydride (B: 6.3 mol) was added and the stirring was continued for 1 h. The sol was dried in an oven at 120 ° C for 5 h and calcined at 500 ° C for 2 h to obtain composition 2.

[0058] Composition 3

[0059] 1333.40 g of aluminum chloride (Al: 10 mol) was dissolved in 1 L of water under stirring, and 6533.33 g of 30 wt% phosphoric acid (P: 20 mol) was added dropwise under stirring to form a homogeneous sol. The stirring was continued for 2 h, and then 653.18 g of ammonium borate (B: 10.54 mol) was added. The stirring was continued for 1 h. The sol was dried in an oven at 90 ° C for 10 h and calcined at 450 ° C for 3 h to obtain composition 3.

[0060] Composition 4

[0061] 2129.96 g of aluminum nitrate (Al: 10 mol) was added to 2 L of water under stirring until dissolved, 1633.33 g of 40 wt% phosphoric acid (P: 6.7 mol) was added dropwise to the dissolved aluminum nitrate to form a homogeneous sol, and then 281.05 g of ammonium fluoroborate (B: 2.7 mol) was added and stirring was continued for 0.5 h. The sol was dried in an oven at 110 ° C for 15 h and calcined at 400 ° C for 4 h to obtain composition 4.

[0062] Composition 5

[0063] 1333.40 g aluminum chloride (Al: 10 mol) was dissolved in 1 L water under stirring, and 6533.33 g 30 wt% phosphoric acid (P: 20 mol) was added dropwise under stirring to form a homogeneous sol. The stirring was continued for 2 h. The sol was dried in an oven at 120°C for 10 h and ground into powder.

[0064] 217.28 g of boric acid (B: 3.51 mol) was dissolved in 500 mL of water, added to the above powder and immersed for 1 h, dried at 120° C. for 5 h, and calcined at 450° C. for 3 h to obtain composition 5.

[0065] Comparative composition 1

[0066] 1019.60 g of dry pseudo-boehmite (Al: 20 mol) was dispersed in 3 L of water under stirring, and stirring was continued for 0.5 h. 1960.00 g of 50 wt% phosphoric acid (P: 10 mol) was added dropwise under stirring, and stirring was continued for 1 h. Then 274.11 g of boric anhydride (B: 7.9 mol) was added, and stirring was continued for 1 h. The sol was dried in an oven at 100 ° C for 12 h to obtain a comparative composition 1.

[0067] Comparative composition 2

[0068] 2129.96 g aluminum nitrate (Al: 10 mol) was added to 3 L water under stirring until dissolved, and then 61.83 g boric acid (B: 1 mol) was added and stirring was continued for 0.5 h. The mixture was dried in an oven at 80 ° C for 24 h and calcined at 700 ° C for 1 h to obtain comparative composition 2.

[0069] Comparative composition 3

[0070] 1019.60 g of dry pseudo-boehmite (Al: 20 mol) was dispersed in 3 L of water under stirring and the stirring was continued for 0.5 h. 1400.00 g of 70 wt% phosphoric acid (P: 10 mol) was added dropwise under stirring to form a homogeneous sol. The stirring was continued for 1 h. The sol was dried in an oven at 120 ° C for 5 h and calcined at 500 ° C for 2 h to obtain comparative composition 3.

[0071] The compositions of compositions 1-5 and comparative compositions 1-3 and the corresponding partial preparation conditions are shown in Table 2.

[0072] Table 2 Compositions and preparation conditions of compositions 1-5 and comparative compositions 1-3

[0073]

[0074] Example 1

[0075] In this embodiment, composition 1 is used to prepare catalytic cracking catalyst S1, comprising the following steps:

[0076] In a reactor with water bath heating, 2.5L of water, 870g of kaolin, 150g of pseudo-boehmite, and 600g of composition 1 were added, and then 90g of hydrochloric acid was slowly added and mixed evenly. After stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1666g of aluminum sol was added to form a catalyst matrix slurry; 2L of water was added to a pulping tank, and 1080g of RDSY molecular sieve was added. After passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry. After pulping for 1 hour, the resulting microspheres were spray-formed and calcined at 500°C for 1 hour, washed with water, and dried in an oven at 120°C for 8 hours to obtain catalyst S1.

[0077] Example 2

[0078] This example uses composition 2 to prepare catalytic cracking catalyst S2, comprising the following steps:

[0079] In a reactor with water bath heating, add 2L of water, 660g of enamel, and 450g of composition 2, mix well, stir for 1 hour, age at 75°C for 1h, and then add 2166g of aluminum sol to form a catalyst matrix slurry; add 1.7L of water to a pulping tank, add 1260g of RDSY+240g of ZSM-5 molecular sieve, pass through a high-speed shearing machine for 20min, add to the catalyst matrix slurry, pulp for 1h, and then spray mold, and the obtained microspheres are calcined at 400°C for 3 hours, washed with water, and dried in an oven at 100°C for 20h to obtain catalyst S2.

[0080] Example 3

[0081] This example uses composition 3 to prepare catalytic cracking catalyst S3, comprising the following steps:

[0082] In a reactor with water bath heating, 3.5L water, 1140g montmorillonite, 150g composition 3 and 390g pseudo-boehmite were added and mixed evenly, 190g hydrochloric acid was added dropwise, and after stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1333g aluminum sol was added to form a catalyst matrix slurry; 4L water was added to a pulping tank, and 980g RDSY+100g REY molecular sieves were added. After passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry, and after pulping for 1 hour, the resulting microspheres were spray-formed and calcined at 800°C for 0.5 hour, washed with water, and dried in an oven at 150°C for 8 hours to obtain catalyst S3.

[0083] Example 4

[0084] This embodiment uses composition 4 to prepare catalytic cracking catalyst S4, comprising the following steps:

[0085] In a reactor with water bath heating, 2.5L water, 1620g attapulgite, 300g composition 4 and 180g pseudo-boehmite were added and mixed evenly, 90g hydrochloric acid was added dropwise, and after stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1333g aluminum sol was added to form a catalyst matrix slurry; 3.5L water was added to a pulping tank, and 600g β molecular sieve was added, which was passed through a high-speed shearing machine for 20 minutes and then added to the catalyst matrix slurry. After pulping for 1 hour, the resulting microspheres were spray-formed and calcined at 500°C for 1 hour, washed with water, and dried in an oven at 120°C for 15 hours to obtain catalyst S4.

[0086] Example 5

[0087] This embodiment uses composition 5 to prepare catalytic cracking catalyst S5, comprising the following steps:

[0088] In a reactor with water bath heating, 3.5L water, 840g kaolin, 450g composition 5 and 240g pseudo-boehmite were added and mixed evenly, 120g hydrochloric acid was added dropwise, and after stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1125g silica sol was added to form a catalyst matrix slurry; 3.0L water was added to a pulping tank, and 800g RDSY+280g REY molecular sieves were added, and after passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry, and after pulping for 1 hour, the resulting microspheres were spray-formed and calcined at 500°C for 1 hour, washed with water, and dried in an oven at 100°C for 24 hours to obtain catalyst S5.

[0089] Example 6

[0090] This example uses composition 2 to prepare catalytic cracking catalyst S6, comprising the following steps:

[0091] In a reactor with water bath heating, 4L of water, 1050g of kaolin, 4240g of composition 2, and 270g of pseudo-boehmite were added and mixed evenly, 130g of hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1 hour, and then 900g of silica sol was added to form a catalyst matrix slurry; 4L of water was added to a pulping tank, and 1080g of RDSY molecular sieve was added. After passing through a high-speed shearing machine for 20 minutes, it was added to the catalyst matrix slurry. After pulping for 1 hour, it was spray-formed, and the obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried in an oven at 120°C for 18 hours to obtain catalyst S6.

[0092] Comparative Example 1

[0093] This comparative example prepares catalytic cracking catalyst D1, in which no boron-phosphorus-aluminum composition is used, comprising the following steps:

[0094] In a reactor with water bath heating, add 2.5L water, 1470g kaolin, 150g pseudo-boehmite, then slowly add 90g hydrochloric acid and mix evenly. After stirring for 1 hour, age at 75°C for 1h, and then add 1666g aluminum sol to form a catalyst matrix slurry; add 2L water to a pulping tank, add 1080g RDSY molecular sieve, pass through a high-speed shearing machine for 20min, add to the catalyst matrix slurry, pulp for 1h, and then spray mold. The obtained microspheres are calcined at 500°C for 1 hour, washed with water, and dried in an oven at 120°C for 8h to obtain catalyst D1.

[0095] Comparative Example 2

[0096] This comparative example prepares catalytic cracking catalyst D2, wherein boric acid is used instead of the boron-phosphorus-aluminum composition, comprising the following steps:

[0097] In a reactor with water bath heating, add 2.5L water, 1470g kaolin, 150g pseudo-boehmite, 422g boric acid, then slowly add 90g hydrochloric acid and mix evenly. After stirring for 1 hour, age at 75°C for 1h, and then add 1666g aluminum sol to form a catalyst matrix slurry; add 2L water to a pulping tank, add 1080g RDSY molecular sieve, pass through a high-speed shearing machine for 20min, add to the catalyst matrix slurry, pulp for 1h, and then spray mold. The obtained microspheres are calcined at 500°C for 1 hour, washed with water, and dried in an oven at 100°C for 24h to obtain catalyst D2.

[0098] Comparative Example 3

[0099] This comparative example uses comparative composition 1 to prepare catalytic cracking catalyst D3, comprising the following steps:

[0100] In a reactor with water bath heating, 3.5L water, 840g kaolin, 450g comparison composition 1, and 240g pseudo-boehmite were added and mixed evenly, 120g hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1 hour, and then 1125g silica sol was added to form a catalyst matrix slurry; 3.0L water was added to a pulping tank, and 1080g RDSY molecular sieve was added. After passing through a high-speed shearing machine for 20 minutes, it was added to the catalyst matrix slurry. After pulping for 1 hour, it was spray-formed, and the obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried in an oven at 150°C for 8 hours to obtain catalyst D3.

[0101] Comparative Example 4

[0102] This comparative example prepares catalytic cracking catalyst D4, wherein a sol containing boron, phosphorus and aluminum is used instead of the boron-phosphorus-aluminum composition of the present invention, comprising the following steps:

[0103] 773.37 g of aluminum chloride was dissolved in 500 L of water under stirring, and 1421 g of 80 wt% phosphoric acid and 49 g of boric acid were added dropwise under stirring to form a homogeneous sol. Stirring was continued for 2 h to obtain Sol A.

[0104] In a reactor with water bath heating, 2.0L water, 840g kaolin and 240g pseudo-boehmite were added and mixed evenly, 120g hydrochloric acid was added dropwise, and the above-obtained sol A was added. After stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1125g silica sol was added to form a catalyst matrix slurry. 3.0L water was added to a beating tank, and 800g RDSY+280g REY molecular sieves were added. After passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry. After beating for 1 hour, the obtained microspheres were spray-formed and calcined at 800°C for 0.5 hour and dried in an oven at 120°C for 20 hours to obtain catalyst D4.

[0105] Comparative Example 5

[0106] This comparative example uses comparative composition 2 to prepare catalytic cracking catalyst D5, comprising the following steps:

[0107] In a reactor with water bath heating, 3.5L water, 840g kaolin, 450g comparative composition 2, and 240g pseudo-boehmite were added and mixed evenly, 120g hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1 hour, and then 1125g silica sol was added to form a catalyst matrix slurry; 3.0L water was added to a pulping tank, and 800g RDSY+280g REY molecular sieves were added. After passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry. After pulping for 1 hour, it was spray-formed, and the obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried in an oven at 120°C for 8 hours to obtain catalyst D5.

[0108] Comparative Example 6

[0109] This comparative example uses comparative composition 3 to prepare catalytic cracking catalyst D6, comprising the following steps:

[0110] In a reactor with water bath heating, 3.5L water, 840g kaolin, 450g comparison composition 3, and 240g pseudo-boehmite were added and mixed evenly, 120g hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1 hour, and then 1125g silica sol was added to form a catalyst matrix slurry; 3.0L water was added to a pulping tank, and 800g RDSY+280g REY molecular sieves were added. After passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry. After pulping for 1 hour, it was spray-formed, and the obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried in an oven at 100°C for 24 hours to obtain catalyst D6.

[0111] Comparative Example 7

[0112] This comparative example prepares catalytic cracking catalyst D7, wherein boric acid and phosphoric acid (both account for 1 wt% of the catalyst dry basis) are used instead of the boron-phosphorus-aluminum composition, comprising the following steps:

[0113] In a reactor with water bath heating, add 2.5L water, 1470g kaolin, 150g pseudo-boehmite, then slowly add 90g hydrochloric acid and 422g boric acid and mix evenly. After stirring for 1 hour, age at 75°C for 1h, then add 1666g aluminum sol and 358g 85wt% phosphoric acid to form a catalyst matrix slurry; add 2L water to a pulping tank, add 800g RDSY+280gREY molecular sieve, pass through a high-speed shearing machine for 20min, add to the catalyst matrix slurry, pulp for 1h, and then spray mold. The obtained microspheres are calcined at 500°C for 1 hour, washed with water, and dried in an oven at 100°C for 24h to obtain catalyst D2.

[0114] The composition of the above catalysts S1-S6 and the following D1-D7 is shown in Table 3 below, the activity data is shown in Table 4 below, and the ACE evaluation results of each catalyst contaminated sample (contaminated with 12000 ppm nickel) are shown in Table 5.

[0115] Table 3 Composition of raw materials corresponding to each component in the catalyst obtained in the examples and comparative examples (on a dry basis of oxides)

[0116]

[0117] Table 4 Catalyst activity (MAT, 800℃×17h)

[0118] Catalyst No. S1 S2 S3 S4 S5 S6 D1 D2 D3 D4 D5 D6 D7 Catalyst activity 62 63 62 63 61 63 63 57 59 58 57 62 59

[0119] As can be seen from Table 4, the catalysts S1-S6 of the embodiment still have relatively high activity after 800°C × 17h ​​water vapor aging, while the activity of the catalysts D2, D3, and D4 of the comparative examples decreases significantly, indicating that the addition method of boron (B) has an effect on the structure of the molecular sieve. The presence of AlPO4 in the boron-phosphorus-aluminum composition of the present invention can effectively inhibit the dealumination of the molecular sieve, offset the toxic effect of the addition of B on the catalyst, and at the same time, during the preparation process of the boron-phosphorus-aluminum composition, a mesoporous structure is formed by roasting, and boron is fixed in the pores of the composition. It is not easy to migrate to the surface of the molecular sieve during the preparation process of the catalyst, destroying the skeleton structure of the molecular sieve, so that the catalysts S1-S6 can still maintain relatively high activity stability after 800°C × 17h ​​water vapor aging. Catalyst D2 uses boric acid instead of the boron-phosphorus-aluminum composition, catalyst D3 uses the uncalcined comparative composition 1, catalyst D4 uses a sol containing boron, phosphorus, and aluminum instead of the boron-phosphorus-aluminum composition of the present invention, D5 uses the phosphorus-free composition 2, and D7 uses the form of directly adding phosphoric acid and boric acid, all of which show a significant decrease in activity. Catalyst D1 was used as a blank control without adding any composition or other B substitutes. D6 used the boron-free comparative composition 3.

[0120] Table 5 ACE evaluation results of various catalyst contaminated samples

[0121]

[0122] As can be seen from Table 5, after the catalyst was contaminated with 12000ppm nickel, the conversion rate of the catalyst sample of the embodiment was relatively high, and the H2 / CH4 ratio was relatively low compared with the catalysts D1 and D6 of the comparative examples, indicating that the addition of the boron-phosphorus-aluminum composition of the present invention can fix the nickel metal, thereby inhibiting the dehydrogenation produced by it, so that the H2 / CH4 ratio is relatively low, and there is a certain nickel resistance. Compared with comparative examples D2, D3, D4, D5, D6, and D7, examples S1-S2 have relatively high conversion rates, indicating that the negative impact of adding the boron-phosphorus-aluminum composition on the catalyst in the manner of the embodiment is minimal.

[0123] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing a catalytic cracking catalyst resistant to heavy metal nickel pollution, wherein: The preparation method comprises the following steps: The first raw material is mixed with water, slurried, and then spray-formed, roasted, washed, and dried to obtain the catalytic cracking catalyst; The first raw material includes a boron-phosphorus-aluminum composition, a molecular sieve, clay and a binder; The boron-phosphorus-aluminum composite is a mixture of AlPO4 and B, P, and Al, and is calcined during the preparation process.

2. The preparation method according to claim 1, wherein The first raw material also includes pseudo-boehmite.

3. The preparation method according to claim 1, wherein The boron-phosphorus-aluminum composite is prepared by reacting an aluminum compound, phosphoric acid, and a boron compound and calcining at 400-700°C; The boron compound is added according to the boron content of the total mass of the boron-phosphorus-aluminum composition being 2 wt% to 6 wt%; The aluminum compound and phosphoric acid are added in a molar ratio of Al:P of (0.5-2.0):

1.

4. The preparation method according to claim 3, wherein The boron-phosphorus-aluminum composition is prepared by the following method 1 or method 2: Method 1: Add aluminum compound to water, then add phosphoric acid dropwise; then add boron compound and stir to obtain a sol containing boron, phosphorus and aluminum; Drying the sol containing boron, phosphorus and aluminum, and calcining to obtain the boron-phosphorus-aluminum composite; Method 2: adding an aluminum compound to water, and then dropping phosphoric acid to obtain a sol containing phosphorus and aluminum; drying the sol containing phosphorus and aluminum to obtain an intermediate product; The boron compound is dissolved in water, loaded in the intermediate product by an impregnation method, dried, and calcined at 400 to 700° C. for 1 to 4 hours to obtain the boron-phosphorus-aluminum composite.

5. The preparation method according to claim 3 or 4, wherein The aluminum compound is selected from one or a combination of two or more of aluminum oxide, pseudo-boehmite, aluminum nitrate, and aluminum chloride.

6. The preparation method according to claim 4, wherein The boron compound is selected from one or a combination of two or more of boron phosphate, boric acid, boric anhydride, ammonium borate, and ammonium fluoroborate.

7. The preparation method according to any one of claims 1 to 4, wherein: The specific preparation process of the catalytic cracking catalyst includes: Adding the second raw material into water and mixing evenly, adding a binder after aging to form a catalyst matrix slurry; the second raw material includes the boron-phosphorus-aluminum composition and clay, or the second raw material includes the boron-phosphorus-aluminum composition, clay and pseudo-boehmite; The molecular sieve is added into water, sheared, and then added into the catalyst matrix slurry, slurried, spray-formed, calcined, washed, and dried to obtain the catalytic cracking catalyst.

8. The preparation method according to claim 1, wherein The calcination temperature of the catalytic cracking catalyst is 400-800° C., and the calcination time is 0.5-3 hours.

9. The preparation method according to claim 2, wherein: The corresponding raw materials of each component in the obtained catalytic cracking catalyst are calculated on a dry basis as follows: the content of the molecular sieve is 20wt% to 50wt%, the content of the boron-phosphorus-aluminum composition is 5wt% to 25wt%, the content of the clay is 19wt% to 55wt%, the content of the pseudo-boehmite is 0 to 13wt%, and the content of the binder is 8wt% to 15wt%.

10. The preparation method according to claim 1, wherein: The molecular sieve is selected from one or a combination of two or more of RDSY molecular sieve, REY molecular sieve, β molecular sieve and ZSM-5 molecular sieve.

11. The preparation method according to claim 1, wherein: The clay is selected from one or a combination of two or more of kaolin, elosite, montmorillonite and attapulgite.

12. The preparation method according to claim 1, wherein: The binder is selected from one or a combination of two or more of aluminum sol, silica sol or colloidal aluminum oxide or silicon oxide materials.

13. A catalytic cracking catalyst resistant to heavy metal nickel pollution prepared by the preparation method according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Catalytic cracking catalyst for increasing diesel yield and preparation method of catalytic cracking catalyst

    CN108499600A

  • Modified aluminum oxide, preparation method of modified aluminum oxide and catalyst containing modified aluminum oxide

    CN111744514A

  • Method of manufacturing a hydrorefining catalyst

    GB1602184A

  • Protection of solid acid catalysts from damage by volatile species

    US20070004953A1